IMPLEMENTASI PROGRAM TAHFIDZUL QURAN DALAM MEMBENTUK KARAKTER DISIPLIN DAN TANGGUNGJAWAB DI SMPIT INSAN CENDEKIA SINGKEP - Cici Angraini; Selamat; Muhammad Syahwandi (Sekolah Tinggi Ilmu Tarbiyah (STIT) Lingga, 2025)
This study aims 1) to determine the implementation of the Tahfidzul Qur'an program in shaping the discipline and responsibility character of students at SMPIT Insan Cendekia Singkep, and 2) to identify the supporting and inhibiting factors in implementing the Tahfidzul Qur'an program at SMPIT Insan Cendekia Singkep. This research uses a qualitative method with a case study. Data were collected through observation, in-depth interviews, and documentation involving the school principal, tahfidz teachers, and students. The data analysis technique used was Miles and Huberman's qualitative analysis technique. The results of the study show that the implementation of the Tahfidzul Qur'an program in fostering the discipline and responsibility character of students at SMPIT Insan Cendekia Singkep is carried out systematically through grouping students based on their ability to read the Qur'an and the use of the wafa method in memorization, muroja'ah (review), and tajwid learning. This program is effective in shaping discipline, as reflected in achieving memorization targets, arriving on time, obeying school regulations, and completing tasks within the specified time. The program also develops responsibility character, such as consistency in maintaining memorization, completing tasks, and being accountable for their actions. The supporting factors of this program include the quality of teachers, adequate school facilities, and supervision and support from parents. On the other hand, the inhibiting factors include the lack of student readiness, insufficient number of Qur'an teachers, a lack of parental supervision at home.